TANTANGAN KARAKTER DI ERA REVOLUSI INDUSTRI 4.0 DALAM MEMBENTUK KEPRIBADIAN MUSLIM - Pratama, Dian Arif Noor (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Indonesia as a nation-state and ethnic group that the majority is Muslim, has many of heritage value that can shape its personality into a superior character. Seeing the phenomenon of the industrial era 4.0 as if forgetting the character values as human identity which inevitably lost the divine values. To build the nation's next generation with good character is the responsibility of all lines of life, because education is truly our shared responsibility, for sure this is not an easy matter, therefore awareness of all parties is needed that character education is very important to be implemented. Although all parties are responsible for character education, but the family is the central pillar as the first means for instilling character education so that a solid Muslim personality is shaped. Family failure in instilling character values towards a child will complicate other institutions outside of the family (including schools) in an effort to improve the character of the child. Transfer of habituation based values is an alternative process that must be carried out continuously, so that the formation of children's character individually, restoring divine values in Muslim personality. thus it will form socio-culture in society and socio-cultural shape the country that has character.